Advanced mass spectrometry : applications in organic and analytical chemistry - Schlunegger, Urs P. (Pergamon Press, 1980)
Advanced Mass Spectrometry: Applications in Organic and Analytical Chemistry discusses the concepts that are essential in the effective utilization of mass spectrometry. The title particularly covers the fundamentals of the modern techniques, along with the technological concerns of mass spectrometry. The opening chapter of the selection introduces mass spectrometry, while the subsequent chapters cover the fundamentals and hardware. The next chapters talk about the analytical chemistry consequences and the ion-genetic relationships. The remaining chapter covers the application of mass spectrom.